Determination of actual characteristic curve of main ventilation fan at Quang Ninh underground coal mines using field measurement method - Van Chi Dao; Tien Dung Le; Xuan Ha Tran (Vietnam Journal of Earth Sciences, 2021)
Determining a proper operation mode of the main ventilation fan at an underground coal mine primarily uses the theoretical characteristic curves of the fan’s manufacturer. Because these curves are developed in laboratory-standard conditions, the characteristic curves under different conditions in practice significantly change, seriously impacting the ventilation efficiency and environmental safety of mine. This paper presents a determination of the main fan’s actual characteristic curve using a field measurement method. The method involves the (i) simultaneous measurement of airflow and air pressure at designated locations in fan drift and ventilation crosscut and (ii) statistical analysis and interpolation of the measured data. The results show that the fan actual pressure curve is permanently displaced to the left and steeper than the corresponding theoretical pressure curve in an on-site operating mode. The finding points out that on-site fans operate in overload mode that can quickly damage their mechanical components. This method provides mining engineers with an easy-to-apply tool for proper adjustment of the operation mode. This improves ventilation efficiency, increases environmental safety, and reduces the underground coal mine operational costs.